Mycobacterium ulcerans Disease with Unusual Sites Not to Be Ignored - Sangaré Abdoulaye; Kourouma Sarah Hamdan; Kouassi Yao Isidore; Ecra Elidjé Joseph; Kaloga Mamadou; Gbery Ildevert Patrice (Dermatology Research and Practice)
Objective. The usual preferential site of BU is in the limbs. In our experience, we noticed atypical and often misleading sites which pose serious issues for the diagnosis and often for the treatment. Methods. This is a retrospective study conducted over a period of ten years of BU treatment at the Department of Dermatology of the University Teaching Hospital of Treichville (Abidjan, Côte d’Ivoire). We included in this study all BU cases with atypical site diagnosed clinically and confirmed either by the histology, by smear, or by PCR. Results. Epidemiologically, the age of patients ranged from 3 to 72 years with a median age of 14.2 years. Children aged less than 15 years were affected in almost 80% of case. The clinical table was dominated by ulcerated forms in 82.1% of cases. The unusual topography mostly observed was that of the torso (thorax, back, and abdomen) in 76.8% of cases. Conclusion. BU is an endemic disease in Côte d’Ivoire where it constitutes a serious public health issue. Several years following its first cases, BU still is little known. This dermatosis may present atypical misleading clinical aspects which must be ignored.